Antibiotic Prescribing Trends in an Omani Paediatric Population - Khalid Al-Balushi; Fatma Al-Ghafri; Fatma Al-Sawafi; Ibrahim Al-Zakwani (Sultan Qaboos University Medical Journal, 2014)
Objectives: This study aimed to evaluate antibiotic prescribing patterns for paediatric patients at Sultan Qaboos University Hospital (SQUH), a tertiary care hospital in Muscat, Oman. Methods: This retrospective cross-sectional study included all 1,186 prescriptions issued for 499 patients at the paediatric outpatient clinic and paediatric inpatient ward at SQUH between March and May 2012. Results: Of the 499 patients, 138 (27.6%) were prescribed a total of 28 different antibiotics. A total of 185 (15.6%) antibiotic prescriptions were issued among the total drug prescriptions. Preschool children aged 0–6 years were prescribed antibiotics most frequently (n = 110). Co-amoxiclav was the most commonly prescribed antibiotic in both inpatients and outpatients (27.0% and 33.9%, respectively), followed by cefuroxime in inpatients (13.5%) and azithromycin in outpatients (18.6%). Co-amoxiclav was the most commonly prescribed antibiotic in both 0–6 (31.3%) and 7–11 (23.3%) year-olds, while cefuroxime was most commonly prescribed in children ≥12 years old (25.0%). Conclusion: Antibiotic prescription patterns in this population were similar to those in North America, Europe and Asia. To confirm the findings of this study, further research on antibiotic prescription trends across the wider paediatric population of Oman should be initiated.